Attitude of Iranian Students towards Learning the English Language - Kazemi Malekmahmudi, Maryam; Kazemi Malekmahmudi, Shima (Journal of clinical and basic research, 2018)
Introduction: Attitude is one of the fundamental issues in determining the success of students. It is related to a person’s values and beliefs and promotes or discourages the choices made in both academic career and social life.The purpose of this study was to investigate the effect of gender and field of study on students’ attitude towards learning the English language. Materials and methods: A questionnaire was adopted from a previous study to evaluate attitude of 33 human sciences and medical sciences students selected from the Mazandaran University and Golestan University of Medical Sciences, respectively. Results: Gender had no significant impact on the behavioral, cognitive and emotional aspects of attitude. Field of study had a significant impact on the behavioral and cognitive aspects of attitude but not on the emotional aspect. Conclusions: Since English is an obligatory subject for the majority of EFL learners, teachers are ought to motivate the learners by highlighting the importance of English for their academic achievement. Engaging students in activities that are matched with their needs and interests can also improve the attitude towards English.